Pengaruh Penggunaan QRIS Terhadap Efisiensi Transaksi pada Pelaku Usaha Halal dalam Perspektif Ekonomi Syariah - Abelia Yusnia; Muhammad Rasyad Al Fajar; Ibrahim Ibrahim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study analyzes the effect of using the Quick Response Code Indonesian Standard (QRIS) on transaction efficiency among halal business actors in Bima Regency from the perspective of Islamic economics. Payment digitalization is essential for MSMEs because it can improve competitiveness, business effectiveness, and the quality of transaction services. However, QRIS implementation in Bima Regency still faces several challenges, such as low digital literacy and the dominance of cash-based payment habits. This study employed a quantitative associative-causal approach with a sample of 25 halal business actors selected using purposive sampling. Primary data were collected through a Likert-scale questionnaire and analyzed using simple linear regression with SPSS. The Pearson correlation test showed a strong positive relationship between QRIS use and transaction efficiency, with r = 0.749 and p < 0.05. The regression equation Y = 0.802 + 0.745X indicates that increased QRIS use can improve transaction efficiency. The R-square value of 0.561 indicates that QRIS contributes 56.1% to transaction efficiency. These findings support the Technology Acceptance Model and transaction cost theory. From the perspective of Islamic economics, QRIS supports transparency, justice, and wealth protection (hifz al-mal) through well-documented transactions. Therefore, QRIS has a positive and significant effect on transaction efficiency, particularly in financial recording and cost efficiency.